Organic apple juice clarification: Physicochemical and sensory evaluation - Lauret, Richard; Sartori, Maria Márcia Pereira [UNESP]; Imaizumi, Vitor Massami [UNESP]; Brunelli, Luciana Trevisan [UNESP]; Venturini Filho, Waldemar Gastoni [UNESP] (Universidade Federal do Paraná, 2018)
n the Brazilian market of non-alcoholic beverages, apple juice is found clarified or turbid. In addition to its consumption as juice itself and nectar, it can also be used in soft drinks formulation. The aim of this work was to clarify organic apple juice of Eva variety using enzymatic complex (pectinases), gelatin and bentonite (phase 1) and to compare physicochemical and sensorial clarified and unclarified Eva apple juices (phase 2). The experimental design was completely randomized. In phase 1, the tests were performed on bench scale, adopting a factorial schedule and in phase 2, the tests were performed on a pilot plant scale. Parameters such as soluble solids, titratable acidity, ratio, pH, reducing sugars, total reducing sugars, non-reducing sugars, phenolic compounds, turbidity and color were evaluated for the physicochemical characterization of juices. The sensory analysis of juices were performed by affective test (hedonic scale). In phase 1, the best juice clarification results were obtained using the enzymatic complex, gelatin at concentrations of 8, 10 and 12 g.100 L-1 and bentonite at 50 g.100 L-1, with final juice filtration in paper of 28 μm pore. In phase 2, the clarification process interfered on physicochemical characteristics of the juice for all analyzed parameters, except for total reducing sugars and non-reducing sugars. Despite differences in physicochemical composition, the panel of tasters showed equal acceptability between clarified and unclarified juices.
Clarificação de suco de maçã orgânica: Avaliação físico-química e sensorial
Keywords: Bentonite; Enzymatic complex; Malus domestica; Non-alcoholic beverage; Pectinases